Control interno y su incidencia en la gestión administrativa de la empresa alta producción Altaproduc S.A., cantón Babahoyo, año 2012 - España Alarcón, Félix Rafael (2015)
In this research project Alta Producción Altaproduc S.A.It is located in Union Parish Clementina, Abraham Freire Street, City Babahoyo, Los Rios province. The company is dedicated to the purchase and sale of agricultural products; previously it proceeded to the establishment of the general objective: To evaluate the internal control system and its impact on the administrative management of the company Alta Producción Altaproduc S.A., Canton Babahoyo, year 2012, the company has a manager who is responsible for directing and controlling the management is complying fully. Whereby the degree of compliance with the objectives to capture in order to assess the administrative development was evaluated. Through the methods, types and research techniques as: historical, analytical, inductive, documentary research, field, exploratory, descriptive, observational and interview the CEO. By assessing the internal control in accordance with COSO II method, it was determined that in all audit should check the levels of Inherent Risk, which is what must be done to each department as it will have an accepted criterion of how they are managed, if comply with policies and regulations of the company. Internal control of administrative determine a level of inherent risk of 57% in the company Alta Producción Altaproduc S.A. Finally it is concluded that the company has weaknesses in terms of their functions performed by the staff are not very efficient , they come to be the main problem to comply fully with the goals proposed by the company could also be observed could be observed the company has weaknesses in their controls, it is taken for errors of estimates what your income and expenses for a year , according to the assessment made Alta Produccion Altaproduc S.A. in compliance with laws and regulations it has determined that compliance with the 75 % , because there are laws that have not been considered as part of their duties